The signal of volatility - Till Strohsal; Enzo Weber (Humboldt University of Berlin, Collaborative Research Center 649 - Economic Risk, 2012)
The present study addresses the economic interpretation of stock market volatility. We argue that its character is inherently ambivalent, being considered as an indicator of either information flow or uncertainty.We discriminate between these views by measuring the fraction of price changes that feeds into other markets depending on the prevailing level of volatility. This exploits the revealed reaction of investors to gauge the degree of information and uncertainty ascribed to volatility. We estimate simultaneous timevarying coefficient models, using data of US and further stock markets. We find the signal of volatility to depend crucially on the combination of its sender and receiver.
Keywords: G15; C32; 330; Information; Uncertainty; Spillover; Simultaneous Equations; Identification; Börsenkurs; Volatilität; Informationswert; Spillover-Effekt; Schätzung; Simultanes Gleichungssystem; Aktienmarkt; USA; Welt